HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU MOBILISASI DINI PASIEN POST OPERASI APENDIKTOMI DI RUANG RAWAT INAP RUMAH SAKIT - Susila Wati; Dwi Heppy Rochmawati; Wigyo Susanto (Journal Healthcare Education, 2026)
Early mobilization is an important intervention in post-appendectomy care to accelerate recovery, prevent complications, and improve patient comfort. The implementation of early mobilization is greatly influenced by the patient's level of knowledge regarding the benefits, timing, and implementation techniques. Objective: To determine the relationship between the level of knowledge and early mobilization behavior of post-appendectomy patients in the inpatient ward of Sari Asih Hospital, Serang. Method: This study used a descriptive correlative design with a cross-sectional approach. The sample of the study was 40 post-appendectomy respondents with a total sampling technique. Data were collected using a questionnaire on the level of knowledge and early mobilization behavior, then analyzed bivariately using the Chi-Square test. Results: The results of the Chi-Square test showed that the p-value was 0.000 (p <0.05). So there is a significant relationship between the level of knowledge and early mobilization behavior of post-appendectomy patients in the inpatient ward of Sari Asih Hospital, Serang. Conclusion: There is a relationship between knowledge level and early mobilization behavior of appendectomy patients in the inpatient ward of Sari Asih Hospital, Serang.